A 10 years review of statutory rape cases in HUSM (Retrospective study 2005-2014) - Shukri, Rahilah Ahmad (2017)
Objective: To analyse the demographic data, genital injury, physical and psychological impact among statutory rape survivors aged 10-15 years old, treated in Hospital Universiti Sains Malaysia (HUSM) One Stop Crisis Centre (OSCC) from 2005-2014. Design: Descriptive study, retrospective data collection Material and method: 380 cases were selected randomly from 616 cases of statutory rape treated in HUSM from year 2005-2014, and all important data such as victims’ and assailants’ profile, sexual assault characteristics, findings during physical examination, laboratory results and psychological impact on survivors were documented and analysed. Results: All 380 patients were Malay, and majority of the patients were 15 years old (44.2%). 207 patients (45.5%) had previous sexual exposure; either consented sexual intercourse (86.5%) or previous rape (13.5%). Majority of the victims were raped by known assailants, which was seen in 207 cases (85.2%), and 9.6% were incest. 81% of the cases involved single assailants, followed by 14% being raped by ≥ 3 assailants. All the victims had vaginal penetration, 40.5% had finger penetration, 13.9% had forced oral sex on the assailants and 3.9% had anal penetration. Genital injury prevalence was 94.2%, with multiple genital injury recorded in 85% of the patients. Factors that were associated with multiple genital injuries were unconsented sexual intercourse / rape (p=0.026) age 13-15 years old (p=0.05) and forced oral sex on the assailants (p=0.029). The commonest type of genital injury was tear (79.4%) and hymen was found to be the commonest site of injury among the victims (79.2%). VDRL was reactive in 0.5% of the patients, and no incidence of N.Gonorhoea infection was recorded. 15 patients (3.9%) were pregnant, with majority of the patients were in the third trimester (40%). 61 patients (16%) were diagnosed with psychiatric disorders, and Acute stress disorders recorded to be the highest frequency found among the patients (6.32%).17 patients (28%) with psychiatric disorders were started on treatment and were under psychiatric follow-up. Conclusion: Majority of the patients were sexually abused by known assailants, and sustained multiple genital injury. The prevalence of pregnancy and STI were low, whereas psychiatric disorders were diagnosed in 16% of the patients.